Compatibility analysis between Portland cement type I and micro/nano-SiO2 in the presence of polycarboxylate-type superplasticizers. Issue 1 (31st December 2016) - Zapata Orduz, Luis E.; Portela, Genock; Suárez, Oscar Marcelo; Cáceres, Arsenio D.
Abstract: This study, assessed the interaction between Portland cement type I and polycarboxylate-type superplasticizers. Five systems were analyzed with the cement-superplasticizer pair being selected from the viewpoint of its rheological behavior using the Marsh cone test. The rheological behavior was analyzed using plain and mineral additions of 5, 10 and 15 wt% and 1, 2, and 3 wt% of silica fume (SF) and nanosilica (nS), respectively. Mechanical and rheological validations were carried out in binary-concretes with nS or SF. The results showed that addition of amorphous silica in different particle sizes has very different rheological results. Particularly, in SF-concretes, the samples exhibited higher susceptibility to bleeding and segregation for higher SF amounts. This limited the application of high SP dosages, but this fact induced a premature slump loss even at the early age. In contrast, nS-concretes tended to have less bleeding, increased packing density and enhanced cohesiveness of the cement matrix. Therefore, higher SP dosages were possible. The results also showed that when mineral additions are applied in concrete mixes the Marsh cone test results of cement pastes must be interpreted carefully. For SF-concretes the numerical results were effectively anticipated by using the Marsh methodology. Nevertheless, in nS-concretes the numerical results of SP doses did not reflect the doses of SP anticipated from the Marsh's experiments. Finally, in the hardened state statistical results showed that compressive and splitting tensile strength in some SF/nS-concretes exhibited an increase of up to 35% with respect to control samples.